Participation and Challenges Faced by The women's Elected in Local Level Government at Bharatpur Metropolitan City, Chitwan, Nepal - Sapkota, Keshab Raj (BMC Journal of Scientific Research, 2018)
The study aimed to find out the women’s representation at the local governance level. The paper is a qualitative analysis of participation and challenges of women in local Government in Chitwan, Nepal. This study explored the factors that facilitate women’s access to political and participation in local level governments. This study was based on Interview methods, focus group discussion and key informant interview. The primary information was collected from the 61 elected women who told the story of their journey to political participation and present status at different local level governments. This study was limited within only one Bharatpur Metropolitan City of Chitwan, Nepal. Majority of women lack resources and knowledge of their rights, have to face corrupt political culture and double burden of family role that restrict their effective participation in political processes. Inclusion Policy is the good practices that help advance women’s representation at the local level. The role of family and political parties help in supporting women’s engagement in local politics. The factors to women's political participation that they are mainly linked to low levels of female literacy and training, traditional gender roles and stereotypes, low self-esteem. Women are subject to strong discrimination coming from deeply rooted patriarchal attitudes and practices. There is a widespread belief that the public space is not meant for women and that by nature they cannot be good leaders. These perceptions are stronger in local level politics, making it hard for women to contest and take up leadership positions. The women's participation in local level government has been done to reduce or improve barriers and to analyze the political empowerment of women .